Postponement Of The Death Penalty: An Overview Of Human Rights And Restorative Justice - Husin, Umar (Journal of Law and Policy Transformation, 2024)
The implementation of the death penalty must be carried out with full consideration of the law and existing facts, so that in its implementation the death penalty must be measured and not imposed with careless considerations. One way to prevent errors in administering the death penalty is to provide a time lag between the execution and execution of the death sentence so that the convict is still given the opportunity to defend himself in order to explain the defense which can mitigate it. However, what is happening now is that many death sentences are being carried out with very quick executions. This certainly has an impact on potential violations of the rights of convicts. Therefore, this research will discuss further the retention of the death penalty from a human rights and restorative justice perspective. To analyze the problem, this research use normative method with regulatory, conceptual, and case approach. This research found in postponement of the execution of death row convicts has two jusctification are juridical justification and empirical justification. However, needs special regulation to arrange the posponement and it could be form in presidential regulation.